Implementasi PERPRES 86/2018 tentang Reforma Agraria di Desa Purworejo Kecamatan Donomulyo Kabupaten Malang - Alfan, Zainul (Jurnal Ilmiah Administrasi Publik, 2022)
This research focuses on the implementation of PERPRES number 86 of 2018 concerning agrarian reform in Purworejo Village, Donomulyo District, Malang Regency, which focuses on the land redistribution program. The problem is that until now there has been no clear mechanism of work pattern after land redistribution to then be offered to aid providers. This study uses a qualitative method. The results of this study are that the implementation is still limited to asset management through land redistribution and minimal access management. Only a few beneficiaries had access to capital, and none of the beneficiaries received other assistance. Inhibiting factors: communication, resources, disposition, and bureaucratic structure have an impact on the not optimal implementation of agrarian reform in Purworejo Village.